Effect of Demand-Abilities Fit and Need-Supplies Fit on Performance With Organizational Citizenship Behavior as Mediator at Bung Karno Library Blitar - Christina Nomy Okthaviana; Adya Hermawati; Choirul Anam (Journal of Management Research and Studies, 2026)
This study aims to examine the effect of Demand-Abilities Fit and Need-Supplies Fit on Employee Performance and to analyze the mediating role of Organizational Citizenship Behavior (OCB). The study was conducted among employees of UPT Perpustakaan Proklamator Bung Karno Blitar. The total number of employees was 117, of which 84 were included as the research sample. The sampling technique applied was probability sampling using the proportional sampling method based on work units. Primary data were collected through questionnaires and supported by relevant secondary data. Data analysis employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS version 4.0. The results indicate that Demand-Abilities Fit does not significantly affect employee performance. In contrast, Need-Supplies Fit has a positive and significant effect on employee performance. Demand-Abilities Fit and Need-Supplies Fit both have a positive and significant effect on OCB. Furthermore, OCB has a positive and significant effect on employee performance. Mediation testing reveals that OCB fully mediates the relationship between Demand-Abilities Fit and employee performance, while it partially mediates the relationship between Need-Supplies Fit and employee performance.